Vickers Focus Environmental Choices and Site Location in the Parklands of Southwestern Manitoba - Nicholson, Beverley; Nicholson, Sylvia; Running, Garry; Hamilton, Scott (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThe Vickers Focus people entered the parklands of Southwestern Manitoba sometime around AD 1400, settling in the Tiger Hills uplands. Their ceramics indicate that their original homelands were in south-central Minnesota and northern Iowa and that they maintained connections with the Middle Missouri area to the south. The reconstructed lifeways of the Vickers Focus people, while they were living in this area, indicate that a foraging/horticultural subsistence background influenced their selection of sites. Sometime before AD 1500 they shifted westward into the Lauder Sandhills area southeast of Oak Lake. In their new homeland there is no evidence that they continued to practice horticulture but rather they intensified their foraging activities. While their subsistence strategies appear to have been modified when they relocated themselves, a number of environmental and ecological commonalities link these areas. Both areas are characterized by warm soils, with an abundance of pothole water sources. Ecological complexity and resource richness characterize the local environments. In addition, there appears to have been an active desire to avoid locating their sites along major travel routes in the region. The ecological and environmental parameters of the areas they selected are explored in this paper.